Solving Method of H-Infinity Model Matching Based on the Theory of the Model Reduction - Li Min Zhi; Cao Xin Jun (Institute of Advanced Engineering and Science, 2015)
People used to solve high-order H model matching based on H control theory, it is too difficult. In this paper, we use model reduction theory to solve high-order H model matching problem, A new method to solve H model matching problem based on the theory of the model reduction is proposed． The simulation results show that the method has better applicability and can get the expected performance． DOI: http://dx.doi.org/10.11591/telkomnika.v13i2.6886